Model Kepala Sekolah Wanita di Era Modern - Dinda Khaira Latifa; Muhammad Giatman; Ernawati (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2021)
The role of the principal is very important in the process of continuity and success of an educational institution. The principal needed is the one who can make decisions in various problems that exist in the school environment he leads. Leadership is not limited by gender, as both men and women have the same potential in leading. Therefore, this article aims to find out 1) female leadership gender perspective. 2) Leadership model in a new era. This research method is literature study research and in the collection of data researchers review articles. From the results of the research conducted, the results of the study are: (1) Leadership style can be influenced by gender roles, where gender roles can be categorized into masculine and feminine types. Many equate gender with gender, namely male gender for masculine and feminine for the female gender. (2) Female principal leadership can realize effective leadership because it has excellent and creates effectiveness. Women put more pressure on transformational leadership styles and feminism that involve the participation or views of subordinates as well as others, motivation, and power. A leadership figure that is by era 4.0 where women's leadership needs to act as (1) community-based educational leadership, (2) character-based educational leadership and (3) emotional intelligence in controlling conflict.